Impact of rotation on the geometrical configurations of fossil magnetic fields. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Emeriau, C.; Mathis, S.
Abstract: The MiMeS project demonstrated that a small fraction of massive stars (around 7%) presents large-scale, stable, generally dipolar magnetic fields at their surface. These fields that do not present any evident correlations with stellar mass or rotation are supposed to be fossil remnants of the initial phases of stellar evolution. They result from the relaxation to MHD equilibrium states, during the formation of stable radiation zones, of initial fields resulting from a previous convective phase. In this work, we present new theoretical results, where we generalize previous studies by taking rotation into account. The properties of relaxed fossil fields are compared to those obtained when rotation is ignored. Consequences for magnetic fields in the radiative envelope of rotating early-type stars and their stability are finally discussed.